Integrated genotype–phenotype analysis of long-term epilepsy-associated ganglioglioma - Wang, Yujiao; Wang, Leiming; Blümcke, Ingmar; Zhang, Weiwei; Fu, Yongjuan; Shan, Yongzhi; Piao, Yueshan; Zhao, Guoguang (Brain Pathology, 2021)
The BRAF p.V600E mutation is the most common genetic alteration in ganglioglioma (GG). Herein, we collected a consecutive series of 30 GG specimens from Xuanwu Hospital in order to corroborate the genetic landscape and genotype–phenotype correlation of this enigmatic and often difficult-to-classify epilepsy-associated brain tumor entity. All specimens with histopathologically confirmed lesions were submitted to targeted next-generation sequencing using a panel of 131 genes. Genetic alterations in three cases with histologically distinct tumor components, that is, GG plus pleomorphic xanthoastrocytoma (PXA), dysembryoplastic neuroepithelial tumor (DNT), or an oligodendroglioma (ODG)-like tumor component, were separately studied. A mean post-surgical follow-up time-period of 23 months was available in 24 patients. Seventy seven percent of GG in our series can be explained by genetic alterations, with BRAF p.V600E mutations being most prevalent (n = 20). Three additional cases showed KRAS p.Q22R and KRAS p.G13R, IRS2 copy number gain (CNG) and a KIAA1549-BRAF fusion. When genetically studying different histopathology patterns from the same tumor we identified composite features with BRAF p.V600E plus CDKN2A/B homozygous deletion in a GG with PXA features, IRS2 CNG in a GG with DNT features, and a BRAF p.V600E plus CNG of chromosome 7 in a GG with ODG-like features. Follow-up revealed no malignant tumor progression but nine patients had seizure recurrence. Eight of these nine GG were immunoreactive for CD34, six patients were male, five were BRAF wildtype, and atypical histopathology features were encountered in four patients, that is, ki-67 proliferation index above 5% or with PXA component. Our results strongly point to activation of the MAP kinase pathway in the vast majority of GG and their molecular-genetic differentiation from the cohort of low-grade pediatric type diffuse glioma remains, however, to be further clarified. In addition, histopathologically distinct tumor components accumulated different genetic alterations suggesting collision or composite glio-neuronal GG variants.
CRIS-Team Scopus Importer:2021-08-13
Keywords: BRAF p.V600E; dysembryoplastic neuroepithelial tumor; epilepsy; ganglioglioma; MAP kinase signaling pathway; pleomorphic xanthoastrocytoma